Quality improvement of cast alloys - I. P. Volchok; A. M. Mukhin; S. G. Rjazanov; A. B. Chernjak (Литьë и металлургия)
A brief description of the present situation in foundry production in the Ukraine is given. On the grounds of the analysis of the alloy structure of casting the ways to improve the cast alloys quality are suggested.